To solve the system of equations by substitution, we'll start with the equations given:
- \( x = 5y + 10 \) (Equation 1)
- \( 3x + 8y = -39 \) (Equation 2)
We will substitute the expression for \( x \) from Equation 1 into Equation 2.
Step 1: Substitute \( x \) in Equation 2
Substituting \( x \) in Equation 2:
\[ 3(5y + 10) + 8y = -39 \]
Step 2: Distribute and simplify
Distributing the \( 3 \):
\[ 15y + 30 + 8y = -39 \]
Combine like terms:
\[ 23y + 30 = -39 \]
Step 3: Solve for \( y \)
To isolate \( y \), subtract \( 30 \) from both sides:
\[ 23y = -39 - 30 \]
\[ 23y = -69 \]
Now, divide both sides by \( 23 \):
\[ y = -3 \]
Step 4: Substitute \( y \) back to find \( x \)
Now that we have \( y \), we'll substitute it back into Equation 1 to find \( x \):
\[ x = 5(-3) + 10 \]
\[ x = -15 + 10 \]
\[ x = -5 \]
Conclusion
The solution to the system is:
\[ x = -5 \quad \text{and} \quad y = -3 \]
Let's enter the final answers:
- \( x = -5 \)
- \( y = -3 \)